PAPAN INTERAKTIF SEBAGAI PENDUKUNG SISTEM INFORMASI MANAJEMEN PEMBELAJARAN DI SEKOLAH DASAR ISLAM - Rolla Jayanti, Deasy; Prasetyowati, Firda; Listyo Prabowo, Sugeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid advances in digital resolution have triggered significant transformations in the educational landscape, particularly the transition from conventional teaching approaches to more dynamic and participatory digital technology. Among these technological innovations is the interactive board, which can make the learning process more interactive, collaborative, and student-oriented. This study aims to explore interactive boards as a support for learning management information systems in Islamic elementary schools. This study adopted a qualitative paradigm with a literature review method, analyzing scientific articles and accredited national journals published in the last 5-10 years. The research findings indicate that interactive boards facilitate educators in presenting learning content in a more attractive and dynamic manner, thereby strengthening student learning motivation. Therefore, the researchers concluded that the use of interactive boards has broad prospects for supporting learning management information systems in Islamic elementary schools.